Adaptation pathways for conservation law and policy. (26th September 2018) - McDonald, Jan; McCormack, Phillipa C.; Dunlop, Michael; Farrier, David; Feehely, Jess; Gilfedder, Louise; Hobday, Alistair J.; Reside, April E.
Abstract : Globally, biodiversity is under increasing pressure from human activities despite protective measures in conservation laws. Climate change will exacerbate those pressures and the effects of habitat loss and species decline. Current approaches to conservation law in most countries focus on establishing protected areas and limiting activities outside reserves that might affect priority species, habitats, and ecological communities. These measures have had mixed success depending on scale and implementation, but are likely to perform poorly under conditions of future change. To prepare for the future, we consider how conservation law and policy needs to anticipate and manage for future change; widen its scope beyond species and ecological communities that are currently threatened; and support adaptive management of priority areas and species. Using Australian conservation law as a case study, we outline three possible routes by which this shift could occur. The first involves enhancing the adaptiveness of conservation law, the second expands the focus of conservation law from protected areas and listed species to include ecosystems and ecosystem services, while the third attempts to do both simultaneously. We examine the legal mechanisms needed to implement each route, examples of their use in practice, and barriers that must be overcome for successful implementation. This article is categorized under: Climate, Ecology, and Conservation > Conservation Strategies Abstract : Conservation laws must be more responsive to climate change and expand to conserve more than threatened species and protected areas. We suggest pathways for urgent reform.